Net primary productivity and litter decomposition rates in two distinct Amazonian peatlands - G. C. Dargie; J. del Aguila‐Pasquel; C. J. Córdova Oroche; J. Irarica Pacaya; J. Reyna Huaymacari; T. R. Baker; A. Hastie; E. N. Honorio Coronado; S. L. Lewis; K. H. Roucoux; E. T. Mitchard; M. Williams; et al. (Global Change Biology, 2024)
Measurements of net primary productivity (NPP) and litter decomposition from tropical peatlands are severely lacking, limiting our ability to parameterise and validate models of tropical peatland development and thereby make robust predictions of how these systems will respond to future environmental and climatic change. Here, we present total NPP (i.e., above‐ and below‐ground) and decomposition data from two floristically and structurally distinct forested peatland sites within the Pastaza Marañón Foreland Basin, northern Peru, the largest tropical peatland area in Amazonia: (1) a palm (largely Mauritia flexuosa ) dominated swamp forest and (2) a hardwood dominated swamp forest (known as ‘pole forest’, due to the abundance of thin‐stemmed trees). Total NPP in the palm forest and hardwood‐dominated forest (9.83 ± 1.43 and 7.34 ± 0.84 Mg C ha −1 year −1 , respectively) was low compared with values reported for terra firme forest in the region (14.21–15.01 Mg C ha −1 year −1 ) and for tropical peatlands elsewhere (11.06 and 13.20 Mg C ha −1 year −1 ). Despite the similar total NPP of the two forest types, there were considerable differences in the distribution of NPP. Fine root NPP was seven times higher in the palm forest (4.56 ± 1.05 Mg C ha −1 year −1 ) than in the hardwood forest (0.61 ± 0.22 Mg C ha −1 year −1 ). Above‐ground palm NPP, a frequently overlooked component, made large contributions to total NPP in the palm‐dominated forest, accounting for 41% (14% in the hardwood‐dominated forest). Conversely, Mauritia flexuosa litter decomposition rates were the same in both plots: highest for leaf material, followed by root and then stem material (21%, 77% and 86% of mass remaining after 1 year respectively for both plots). Our results suggest potential differences in these two peatland types' responses to climate and other environmental changes and will assist in future modelling studies of these systems.